Monument in Kentstown (1791)
Drawing of what is probably the carved effigy of Thomas de Tuite of 1363, at Kentstown, County Meath. The monument shows a man dressed in medieval costume, his hands clasped in prayer, head resting on pillow or cushion, dog lying at his feet.
Inscribed in ink and crossed out later l.c.: [...] Kenmare Co.y of Kerry.
Inscribed in ink on verso: 1791.
Inscribed in pencil on verso: Mont. Kentstown / Kents town.
Title inscribed in ink l.c..
Watermark visible l.r..
Irish Topographical Prints & Drawings / Rosalind M. Elmes. - Malton Press, Dublin, 1975
Keywords: Monuments & memorials -- Ireland -- Kentstown (Meath) -- 1790-1800.; Nobility -- Ireland -- Kentstown (Meath) -- 1790-1800.; Stonework -- Ireland -- Kentstown (Meath) -- 1790-1800.; Ink drawings -- Irish -- 1790-1800.; Wash drawings -- Irish -- 1790-1800.